Listening to the Music of a City - Jurková, Zuzana (Lidé města, 2012)
The article consists of two parts. The first is focused on different theoretical approaches used/usable when researching music of a city. The second part offers five topics (which merged on the basis of several criteria): 1) music and the stratified and specialized society; 2) music and rebellion; 3) commodification and music; 4) electronic dance music; 5) music and spirituality. In their frameworks, different musical events and their contexts (“soundscapes”) are discussed. Two important features are recognized when studying Prague soundscapes.The first of them is the blurring of various musical borders (in the concept of music, in style/genre, in the concept of musical sound…). The other feature is the functioning of music in strengthening group identities by fostering internal values and separating them from their surroundings.